2010
DOI: 10.46989/001c.38880
|View full text |Cite
|
Sign up to set email alerts
|

Application and Effectiveness of Immunostimulants, Probiotics, and Prebiotics in Aquaculture: A Review

Abstract: Immunostimulants, also called immunomodulators, adjuvants, or biological response modifiers, stimulate the immune system. They can be administered in the form of drugs or nutrients. Probiotics are organisms or substances that improve the intestinal microbial balance of a host animal. Prebiotics are indigestible components in a diet that are metabolized by specific microorganisms and prove helpful for the growth and health of the host. When provided as dietary supplements in feeds, even in small quantities, imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 37 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Prebiotics resist digestion by the hosts during transit through the GI tract, rather these are fermented by resident microbes, producing bioactive metabolites that lowers the gut pH which in turn, favours proliferation of probiotics such as bifidobacteria and lactobacilli (Vazquez-Olivo et al 2018). Prebiotics may also act as immunostimulants, which improve the host's health via fermentative action by indigenous microflora (Ganguly et al 2010;Song et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Prebiotics resist digestion by the hosts during transit through the GI tract, rather these are fermented by resident microbes, producing bioactive metabolites that lowers the gut pH which in turn, favours proliferation of probiotics such as bifidobacteria and lactobacilli (Vazquez-Olivo et al 2018). Prebiotics may also act as immunostimulants, which improve the host's health via fermentative action by indigenous microflora (Ganguly et al 2010;Song et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that the loss of intracellular potassium ions and other contents will block various metabolic pathways in the cell, reduce the activity of enzymes, and destroy the stability of the membrane (Denyer, 1990). In addition, the membrane permeability of A. hydrophila in the compatibility group was higher than that in the monomer group, indicating that the combination of curcumin and enrofloxacin increased the membrane permeability more easily than that of the monomer (Bai et al, 2009;Ganguly et al, 2010). However, the detailed mechanism needs to be further researched.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is a natural yellow acidic phenol extracted from curcuma genus (Curcumalonga) plant such as turmeric, curcuma (Curcuma L), and acruginous turmeric rhizome (Rhizoma curcumae Aeruginosae) (Aggarwal, et al, 2007). Some recent studies have demonstrated a wide range of pharmacological effects of dietary curcumin, such as elimination of free radicals (Toda et al, 1985) and antioxidant (Ruby et al, 1995), relief of inflammation (Gupta et al, 2011), antibacterial effects, and immunomodulation (Bhuvaneswari & Balasundaram, 2006;Bai et al, 2009;Ganguly et al, 2010). However, only in a few cases the mechanism has been elucidated among their wide biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria Lactobacillus used as probiotics, improved fish health, increased fish digestion process, disease resistance and feed conversion, decreased sensitivity to stress, and improved fish maintenance status [13]. The combination of probiotics and immunostimulants have beneficial effects in aquaculture, such as leading to increased disease resistance and nutrient availability, improved sustainability and profitability of fish production [14].…”
Section: The Monitoring Of Fish Health and Growth During Cultivationmentioning
confidence: 99%